THE EFFECT OF SOCIAL MEDIA USE ON CYBER BULLYING BEHAVIOR - Sherly Avionita; Eca Celia; Zayyan Afif; Fatan Azkia; Fayaddah (Journal of International Islamic Law, Human Right and Public Policy, 2025)
The aim of this study is to seeuse of social media on Cyberbullying behavior among teenagers, and the importance of parental supervision of their children's use of social media, especially in adolescenceto behavioral tendenciescyberbullyingThis study was aimed at class XII Civil Service students at Al-Azhar Medan's flagship high school who use social media. The number of respondents in this study was 21 people. The measuring instrument used in this study wasonline questionnaire via Google FormsThe technique used is a data analysis technique using a qualitative descriptive research design, which is considered the most suitable approach to explore the complex phenomenon of cyberbullying on social media and its impact on the social lives of adolescents. Based on the results of the study, 57.1% said that social media has a positive impact on life, but 23.08% have experienced cases of cyberbullying.cyberbullying. It can be concluded that while social media use offers many benefits, it also increases the risk of cyberbullying. Synergy between schools, families, and the government is needed to provide digital education to adolescents. Socialization regarding internet ethics, empathy, and respect for privacy should be part of the educational curriculum.